2006
DOI: 10.1111/j.1366-9516.2006.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐alpine amphibian distributions related to species palatability to non‐native salmonids in the Klamath mountains of northern California

Abstract: The goal of this study was to examine how introduced trout influence the distributions and abundances of a sub‐alpine amphibian assemblage whose members display a variety of different life‐history and defence strategies. Our study was conducted in the sub‐alpine lentic habitats of three wilderness areas that form the core of the Klamath‐Siskiyou Bioregion of northern California, a biodiversity ‘hotspot’ that supports the highest diversity of sub‐alpine, lentic‐breeding amphibians in the western USA. These wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 39 publications
9
73
0
Order By: Relevance
“…Surveys in the Sierra Nevada have shown that lakes with trout are less likely to be occupied by ranid frogs (Knapp and Matthews 2000;Knapp et al 2003;Knapp 2005) and Pacific chorus frogs Knapp 2005). Similar patterns were observed in the Klamath Mountains, where Cascades frogs (R. cascadae), Pacific chorus frogs, and long-toed salamanders were found to be negatively associated with fish (Welsh et al 2006). The findings of these surveys have been reinforced by fish removal experiments, which have shown that the removal of trout leads to the recovery of ranid frog populations in both the Sierra Nevada (Vredenburg 2004;Knapp et al 2007) and the Klamath (Pope 2008) mountains.…”
Section: Amphibianssupporting
confidence: 55%
“…Surveys in the Sierra Nevada have shown that lakes with trout are less likely to be occupied by ranid frogs (Knapp and Matthews 2000;Knapp et al 2003;Knapp 2005) and Pacific chorus frogs Knapp 2005). Similar patterns were observed in the Klamath Mountains, where Cascades frogs (R. cascadae), Pacific chorus frogs, and long-toed salamanders were found to be negatively associated with fish (Welsh et al 2006). The findings of these surveys have been reinforced by fish removal experiments, which have shown that the removal of trout leads to the recovery of ranid frog populations in both the Sierra Nevada (Vredenburg 2004;Knapp et al 2007) and the Klamath (Pope 2008) mountains.…”
Section: Amphibianssupporting
confidence: 55%
“…The SEM did not support an alternative mechanism, whereby the increased toad growth was due to enhanced phytoplankton abundance in the presence of mosquitofish and we are unaware of a direct interaction where mosquitofish would promote toad tadpoles. There is evidence to suggest that nonnative fish also promote toads in nature; Welsh et al (2006) found western toads to be six times more abundant in the presence of nonnative salmonids in lake and pond habitats in northern California. To date, there are relatively few studies documenting this type of facilitation of native species by invaders through competitive release (e.g., Grosholz 2005).…”
Section: Discussionmentioning
confidence: 99%
“…AICc, Akaike information criterion; SITES, number of water bodies per catchment; AREA, size of the catchment; aELEV, average elevation of water bodies in catchment; aDIST, average distance to nearest water body within catchment; FISHSTATUS, presence of non-native salmonids in at least one water body per catchment. & Marx, 2002;Welsh et al, 2006;Pearson & Goater, 2008). The habitat requirements of fish and A. macrodactylum overlap at high elevations in the northern Rocky Mountains (Howard & Wallace, 1985;Pilliod & Peterson, 2001;Pearson & Goater, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Both species respond to predatory fishes where they co-occur with them (Tyler et al, 1998a;Pilliod & Peterson, 2001;Bull & Marx, 2002;Welsh et al, 2006;Pearson & Goater, 2008), but differences in life history characteristics between A. macrodactylum and R. luteiventris could result in different sensitivities to predatory fish. Both amphibians breed in lakes and ponds ranging from sea level to nearly 3000-m elevation.…”
Section: Target Speciesmentioning
confidence: 99%